The Trp-rich Antimicrobial Amphiphiles With Intramolecular Aromatic Interactions for the Treatment of Bacterial Infection - Wang, Zhihua; Li, Qiuke; Li, Jinze; Li, Jiawei; Shang, Lu; Chou, Shuli; Lyu, Yinfeng; Shan, Anshan (Frontiers in Microbiology, 2021)
The antibiotic-resistance was emerging as the hot issue with the abuse and overuse of antibiotics, and the shortage of effective antimicrobial agents against multidrug resistant bacteria putted forwarded a huge problem to treat the threatening nosocomial skin and soft tissue infection. Antimicrobial peptides exhibited enormous potential as one of the most promising candidates of antibiotic to fight against pathogenic infections because of its unique membrane penetration mechanism to kill pathogens, whereas the clinical application of antimicrobial peptides still face the challenges of production cost, stability, safety and design strategy. Herein, a series of Trp-rich peptides was designed following the principle of paired Trp was plated at ith and ith+4 position on the backbone of peptides, based on the template (VKKX)4, where X represent W, A or L, to study the effect of intramolecular aromatic interactions on the bioactivity of antimicrobial peptides. Through comparing the antimicrobial performance, hemolysis, cytotoxicity and stability, VW5 which equipped with the characters of direct antimicrobial efficacy and physical destruction of bacterial membrane was stood out form the engineering peptides. VW5 also performed well in mice model, which could significantly decrease bacterial colony, the area of dermonecrosis and the inflammation cytokines levels at abscess site without causing toxicity to skin. Overall, this study provides a strategy and template to diminish the randomness in the exploration and design of novel peptides.